(untitled) (Ustozlar uchun, 2025)
Charles Dickens (1812–1870) was one of the most influential novelists of the Victorian era, renowned for his social critique and vivid portrayal of life in 19th-century England. His novels often addressed poverty, child labor, social inequality, and the struggles of the urban poor, exposing the harsh realities of industrial society. Works such as Oliver Twist, Hard Times, and David Copperfield combine narrative storytelling with moral and social commentary. Dickens used memorable characters, intricate plots, and realistic depictions of urban and rural life to highlight injustices and advocate for social reform. His literature reflects both the human consequences of economic and social policies and the Victorian preoccupation with morality, charity, and social responsibility.